Energy Storage Development using Hydrogen and its Potential Application in Colombia - Montenegro, Adriana Rincon; Sanjuan, Marco; Carmona, Mauricio (International Journal of Energy Economics and Policy, 2019)
With the increase in the world population, the needs for energy generation have increased, the biggest contribution for this production comes from fossil fuels, which causes significant negative impacts on the environment and sustainability, such as global warming and stock-outs. In this way, it is essential to develop renewable energy alternatives that gradually replace conventional sources. However, these kinds of sources mostly dependent on environmental conditions, so they have the disadvantage of being intermittent and fluctuating. It is considered that hydrogen can be an attractive option for energy storage maximizing the benefit of renewable energy sources. In the last decades, different technologies have been developed to the use of hydrogen as backup and a renewable energy source. This study provides an inspection of the hydrogen technologies that range from the ways to produce hydrogen from renewable energy sources to their different storage alternatives. It is also presented an outlook of available energy policies and development background in different Latin American countries for power generation using renewable sources. Finally, the analysis focuses its attention in the Colombian potential for several sources (solar, wind, biomass) combined with the use of production and storage technologies for hydrogen as an energy carrier. Keywords: Hydrogen Energy Storage, Hydrogen Production, Renewable Energy, Power-to-Gas JEL Classifications: Q28, Q48, Q58 DOI: https://doi.org/10.32479/ijeep.8294